Analisis Banjir dan Perencanaan Desain Transportasi Sungai di Kota Bojonegoro - Prastica, Rian Mantasa Salve; Maitri, Caya; Nugroho, Pratomo Cahyo; Hermawan, Ade (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
One of the worst problem in Bojonegoro is flood. This research aims to know the factor that could become the factor of flood in Bojonegoro. Besides that, this research analyses the planning of transportation river design in Bojonegoro. Flood discharge analysis uses Nakayasu synthesis unit hydrograph for period of 5 years, 10 years, 25 years, 50 years, and 100 years, then they would be compared to the water maximum capacity that could be loaded by the river. According to the analysis result, Bengawan Solo River in Bojonegoro could not able to load flood discharge from Nakayasu synthesis unit hydrograph analysis for all periods. The result conclusion that captured by HEC-RAS application has the same idea. It shows flood water surface is more than full bank capacity elevation. For river transportation design planning, according to analysis of parameter of depth, width for one and two lanes, turning basin and its depth, the ship design that recommended to ship in the Bengawan Solo River in Bojonegoro are cargo ship and passenger ship with draft of 0.6 m and LOA of 18 m, or the capacity of a passenger ship is 70 people.